The long-distance leader rules for remarkable remote leadership - Kevin Eikenberry and Wayne Turmel (Oakland, California Berrett-Koehler Publishers, Inc, 2018)
The authors' "Three-O" Model refocuses leaders to think about outcomes, others, and ourselves--elements of leadership that remain unchanged, whether employees are down the hall or halfway around the world. By pairing it with the Remote Leadership Model, which emphasizes using technology as a tool and not a distraction, leaders can navigate the terrain of managing teams wherever they are. Filled with exercises that ensure projects stay on track, keep productivity and morale high, and build lasting relationships, this book is the go-to guide for leading effectively, no matter where people work.
Includes bibliographical references and index.
Keywords: Leadership